(untitled) (CIPEEX, 2025)
Introduction: Resistant infections represent a global crisis and make it necessary to search for new therapeutic technologies. The cytotoxic properties of photodynamic therapy have proven to be promising in combating drug-resistant infections. Candida albicans is a microorganism naturally present in the human body but is associated with different types of infections and the development of drug resistance. Objective: To analyze the effect of photodynamic therapy on infections caused by Candida albicans. Method: Articles published since 2019 were collected through PubMed and the Virtual Health Library (BVS), using the terms “antimicrobial blue light” and “Candida albicans.” The most relevant studies were selected, resulting in 10 articles. Results: Favorable cytotoxic effects of phototherapy were observed in combating infections, with the most promising light frequencies ranging between 405 nm and 470 nm. However, higher frequencies such as 660 nm also showed positive results. Different outcomes were observed depending on the exposed species, with C. albicans demonstrating favorable responses. Conclusion: A potent cytotoxic effect was observed between 405 nm and 470 nm against C. albicans.